Aplikasi Service Learning Merdeka Belajar Kampus Merdeka: Mendesain Visi Misi Sekolah dengan Canva - Lisa Nursita; Bambang Sulistyo Edi Purwanto (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Service learning is a method of learning provided to students by combining knowledge obtained formally in the classroom and activities that provide benefits to the community. The purpose of this devotion is to benefit the school through the application of theory that has been obtained by students during the learning process of Computer Technology IV courses by utilizing service learning methods. Lectures are not only sharing knowledge,but also students can directly practice their skills that eventually provide benefits to the school in the form of output, they are the availability of mission-vision billboards with attractive designs and easily accessible to the community, so that schools can get the benefit from the existence of this devotional activity in the form of the availability of mission vision banners with attractive graphic design. The location of the activity is in Pa'Bundunkang State Elementary School and is carried out for 7 days by students by involving lecturers as mentors and teachers as escorts. The method of implementation starts from the stage of preparation, implementation, and strengthening/reflection. The result from this activity is that Pa'Bundukang State Elementary School can renew the appearance of the school's vision-mission as a means to socialize the school's vision-mission to students, school human resources, communities, and stakeholders. In addition, students are able to be more sensitive to social circumstances, and can apply graphic design materials using Canva applications obtained in computer technology iv classes, so that competence of knowledge, skills, and attitudes can be developed.